PENGARUH KETIDAKPUASAN KONSUMEN, CITRA MEREK DAN PERSEPSI HARGA TERHADAP PERPINDAHAN MEREK SEPEDA MOTOR YAMAHA KE HONDA - Nuromavita, Inka; Soliha, Euis (Proceeding SENDI_U, 2016)
So many automotive companies in Indonesia, then consumers will be more selective about which brand ofmotorcycles that will be used as mean of transportation. The problem in this research is â Whether a variableconsumer dissatisfaction, brand image, and perception of price influence on the brand switching from Yamaha toHonda in semarang.The purpose of this research is to analize the variabels consumer dissatisfaction, brand image,and perception of price influence on the brand switching from Yamaha to Honda in Semarang. The samples in thisresearch is 100 respondents, and the methodology used is purposive sampling where the respondent used isconsumers who have switched from a user Yamaha to Honda. The data was collected using a questionnaire. Theresearch showed that the variables of consumer dissatisfaction have positive and significant effect on brandswitching, brand image have positive and significant effect on brand switching and perception of price have positiveand significant effect on brand switching from Yamaha to Honda in Semarang.Kata Kunci: Cunsumer Dissatisfaction, Brand Image, Perseption of Price and Brand Switching